Disengagement, the Palestinian Economy and the Settlements - World Bank (Washington, DC, 2016)
This report stresses that the deep economic crisis in the West Bank and Gaza threatens to impoverish and alienate a generation of young Palestinians. Moreover, today's economic crisis has been caused by restrictions on the movement of Palestinian people and goods, or 'closures', which the Government of Israel (GOI) regards as essential to protecting Israeli citizens from attacks by militants. Without a major reform of the closure regime, however, the Palestinian economy will not revive and Israel's security gains may not be sustainable. The report adds that Israel's Disengagement Plan of June 6 will have very little impact on the Palestinian economy and Palestinian livelihoods, since it only proposes a limited easing of closure. An easing of closures alone, though, will not attract investors back to the Palestinian economy. The review opines that with a freeing-up of the constraints on economic activity and committed Palestinian reform, an additional major donor effort would make a difference - it would enable the Palestinian economy to turn the corner. However, the alternative to this is stark. At the wrong end of the spectrum of possible outcomes is a Palestinian economy with unemployment levels of over 35 percent by 2006, and with poverty afflicting upwards of 55 and 70 percent in Gaza. The study points out that as for the settlement assets that Israel will leave behind, those in Gaza have considerable economic value, and in time can make a significant contribution - provided that Gaza's borders are opened for trade. Prospects for economic recovery will be enhanced if the US and the EU give adequate preference to Palestinian products to help boost exports.